CCAFS Mitigation Options Tool, Beta version - Feliciano D; Nayak D; Vetter, Sylvia H.; Hillier, Jonathan (2018)
The CCAFS Mitigation Options Tool estimates greenhouse gas emissions from multiple crop and livestock management practices in different geographic regions, providing policy-makers across the globe access to reliable information needed to make science-informed decisions about emission reductions from agriculture. CCAFS0MOT joins several empirical models to estimate GHG emissions from different land uses and suggests mitigation options that are compatible with food productions. Researchers at the University of Aberdeen, in partnership with the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the University of Vermont’s Gund Institute of Environment, are developing the tool. CCAFS-MOT has also received support from the United States Agency for International Development (USAID), the United States Department of Agriculture (USDA) and the International Center for Tropical Agriculture (CIAT). CCAFS is carried out with support from CGIAR Fund Donors and through bilateral funding agreements. For details please visit https://ccafs.cgiar.org/donors.